Challenges and Strategies to Develop a Positive Image of the Library - Restanti, Anisa Sri (Record and Library Journal, 2015)
Information technology has been used in the management of the library. There are several libraries have been integrated with the internet to provide services. But the library still image as an institution or an old building that contains the bookshelves and librarian profession under other professions. This article is presented to determine some of the challenges and strategies that can be done in fostering a positive image of the library. Based on the literature study and observation, itâs known, that the challenges are differences in educational background librarians, foster a positive image has not been planned, the development of information technology, the implementation of the code of ethics of librarians is not maximal. In the face of the challenges in creating a positive image, there are strategies that can be done that in terms of internal and external libraries. Thus, it can be concluded that, to foster a positive image of the library is needed strategies and synergies as well as the responsibility of all aspects of the library. Recommendation for librarians are important to develop personal branding. Furthermore, for the library after successfully building a positive image should be able to maintain and restore the image when a crisis.Â Â